2016
DOI: 10.1093/hmg/ddw367
|View full text |Cite
|
Sign up to set email alerts
|

Systemic AAV9 gene therapy improves the lifespan of mice with Niemann-Pick disease, type C1

Abstract: Niemann-Pick disease, type C1 (NPC1) is a heritable lysosomal storage disease characterized by a progressive neurological degeneration that causes disability and premature death. A murine model of NPC1 disease (Npc1-/-) displays a rapidly progressing form of NPC1 disease which is characterized by weight loss, ataxia, increased cholesterol storage, loss of cerebellar Purkinje neurons and early lethality. To test the potential efficacy of gene therapy for NPC1, we constructed adeno-associated virus serotype 9 (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 45 publications
2
52
0
1
Order By: Relevance
“…This would be more helpful to improve longevity. In addition, a very recent study reports that retro-orbital delivery of AAV9-based NPC1 expression under CamKII or EF1a promoters substantially increases the lifespan of NPC1 / mice (39). It will be interesting to compare the effects of various delivering routes, such as intracisternal (40), intracerebroventricular (41), or intracranial injections, on NPC1 expression in the CNS, as well as the reparative effects of AAV9-NPC1 on NPC1 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This would be more helpful to improve longevity. In addition, a very recent study reports that retro-orbital delivery of AAV9-based NPC1 expression under CamKII or EF1a promoters substantially increases the lifespan of NPC1 / mice (39). It will be interesting to compare the effects of various delivering routes, such as intracisternal (40), intracerebroventricular (41), or intracranial injections, on NPC1 expression in the CNS, as well as the reparative effects of AAV9-NPC1 on NPC1 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, gene therapy approaches might be applicable to SCAR16. The obvious solution is to use gene editing approaches to correct these mutations; however, given the recessive nature of the disease, delivery of a functional copy of CHIP may also be beneficial (34,35); alternatively, antisense oligonucleotide therapy that can downregulate mutant CHIP protein levels may also prove to be an effective approach (36).…”
Section: Discussionmentioning
confidence: 99%
“…--SRT (Platt et al, 1997) (Sango et al, 1995) + + AAV (Sargeant et al, 2011;Cachon-Gonzalez et al, 2014), BMT (Norflus et al, 1998;Wada et al, 2000), CM (Pelled et al, 2003), Diet (Denny et al, 2010), HSP (Kirkegaard et al, 2016), MIP-1 (Wu and Proia, 2004), SRT (Jeyakumar et al, 1999) HexB ( Npc1 (−/−) (Morris et al, 1977) + -AAV (Chandler et al, 2017b;Xie et al, 2017;Hughes et al, 2018), AI (Alvarez et al, 2008), AO (Fu et al, 2013), CM (Erickson et al, 2000;Repa et al, 2007;Abi-Mosleh et al, 2009;Liu et al, 2010;Taylor et al, 2012;Hovakimyan et al, 2013;Nusca et al, 2014;Tanaka et al, 2014;Soga et al, 2015;Demais et al, 2016), Diet (Jelinek et al, 2015;Soga et al, 2015), HSP (Chung et al, 2016;Kirkegaard et al, 2016), NS (Griffin et al, 2004;Liao et al, 2009), Transplant (Veyron et al, 1996) Npc1 (Otterbach and Stoffel, 1995) + +…”
Section: Metachromatic Leukodystrophymentioning
confidence: 99%
“…The I1061T mutant, which harbors the most common human NPC1 mutation, was generated to specifically study the effects of proteostatic modulation on disease progression. Various preclinical trials including GT, ERT, and transplant in these models have shown different but promising levels of success in prolonging mutant lifespan, reducing Purkinje cell atrophy and the storage phenotype (Veyron et al, 1996;Soga et al, 2015;Chandler et al, 2017b;Xie et al, 2017;Hughes et al, 2018).…”
Section: Metachromatic Leukodystrophy (Mld Omim #250100)mentioning
confidence: 99%